2007
DOI: 10.1007/s11244-007-9010-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Carbon Monoxide and Methanol Oxidation at Single-crystal Electrodes

Abstract: The electrochemical oxidation of carbon monoxide and methanol on single-crystal noble metal electrodes has been studied using cyclic voltammetry, chronoamperometry, in situ FTIR spectroscopy, online electrochemical mass spectrometry, and theoretical methods. The oxidation of CO was found to be enhanced by steps and defects. Furthermore, the surface diffusion rate was found to have a significant influence on the kinetics of the oxidation process: for high diffusion rates, such as the oxidation of CO on platinum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
146
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(160 citation statements)
references
References 53 publications
12
146
1
1
Order By: Relevance
“…Next, the single crystal was transferred to the de-aerated CuSO 4 and H 2 SO 4 solution. The Cu UPD profile of the crystal was first measured by cycling the crystal between potentials of 0.2 V and 0.45 V at 5 mV s À1 .…”
Section: Experimental Single Crystal Electrochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Next, the single crystal was transferred to the de-aerated CuSO 4 and H 2 SO 4 solution. The Cu UPD profile of the crystal was first measured by cycling the crystal between potentials of 0.2 V and 0.45 V at 5 mV s À1 .…”
Section: Experimental Single Crystal Electrochemistrymentioning
confidence: 99%
“…Steps and defects on Pt are known to decrease the potential for CO oxidation and thereby also help the MOR. 4 Surfaces with relatively weak binding of CO (such as the group 11 metals), however, are not generally able to activate methanol sufficiently. Alloy catalysts have been proposed to overcome these technical issues.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the MOR has been also studied in HClO 4 solution in which perchloric anion is not adsorbed on Pt electrodes as strongly as (bi)sulfate anions. Some papers report the order of the activity for the MOR: Pt(111) < Pt(110) < Pt(100), 3,5,6 whereas Wieckowski et al report the activity series: Pt(111) < Pt(100) ¹ Pt(110).…”
Section: Introductionmentioning
confidence: 99%
“…Gómez et al [16] studied the role of surface heterogeneities (ordered steps and defects) on the oxidation of CO adsorbed at Rh (111) electrodes and found that the more ordered is the Rh(111) surface, the slower the reaction proceeds. Housmanns et al investigated CO electro-oxidation on "ordered" and "disordered" Rh[n(111)-(111)] single crystal electrodes [17][18][19][20][21] and proposed that the CO electro-oxidation follows a Langmuir-Hinshelwood type nucleation and growth mechanism controlled by the slow surface mobility of adsorbed CO. Anions were also shown to play an important role in the CO oxidation mechanism on Rh electrodes [19]. In our electrochemical study of the three low-index Rh single crystal surfaces [22] we demonstrated that the reaction pathway of CO oxidation on all three low-index Rh surfaces proceeds according to the Langmuir-Hinshelwood mechanism and is controlled by the formation of OH ads at steps and defect sites, followed by a complex growth process on terrace sites.…”
Section: Introductionmentioning
confidence: 99%